The Australian Water Sector and the SDGs – A SDG Localization framework for guiding sustainable development leadership - Satur, Paul (2023)
Paul Satur POLICY SEMINAR Water & SDGs - Downscaling WATer relevant SDGs (DWAT-SDGs) 2023 UN Water Conference Side Event Jointly organized with the International Water Resources Association (IWRA) MAR 20, 2023 - 10:00 TO 11:00AM EDT